Minat Belajar Mahasiswa STAB Maitreyawira - Yadi Sutikno; Hosan Hosan; Irawati Irawati (Jurnal Maitreyawira, 2021)
There are still some achievements of STAB Maitreyawira students that still need to be improved. The method in this educational research is a descriptive method. The place in this research is STAB Maitreyawira. The research time is September 2021. Then the population in this study is 38 students of STAB Maitreyawira Class of 2019. Because only 30 students filled out the questionnaire in this study, in this study only data from 30 students were used as subjects in this study. From the results of the calculations, it is found that the average value of student interest in learning for the 2019 batch of S1 Buddhist Religious Education Study Programs STAB Maitreyawira is 76.54. This provides an explanation of student interest in learning, namely the learning interest of STAB Maitreyawira students for the class of 2019 is relatively high (from the calculation (3100 4050) x 100% = 76.54%). The conclusion of this study is that the learning interest of students of the 2019 batch of S1 Buddhist Religious Education Study Program STAB Maitreyawira is relatively high, namely 76.54. KATA KUNCI: minat, belajar, mahasiswa